KONSTRIBUSI STRATEGI BERTAHAN HIDUP RUMAH TANGGA PASCA-TRAGEDI BOM BALI I PADA PENINGKATAN KESEJAHTERAAN MATERI: MENGGUNAKAN DATA PANEL RUMAH TANGGA - Suriastini, N.W. (PIRAMIDA; Vol. 6, No.1 Juli 2010, 2012)
This research is aimed to know the contribution of the household survival strategies in terms ofmedium welfare improvements after the Bali bombing I, 2003-2005, based on the data of NationalSocial Economic Survey (SUSENAS) 2002 and the data panel of the Study Economics SocialTransition in Bali (EST-Bali) 2003, 2004, and 2005 which are specially collected to explore the socioeconomic impacts of Bali bombing 1. The data of SUSENAS and ESST-Bali are analysed in adescriptive way and use multinominal logistic. The result of the analysis is confirmed with thequalitative data from six different locations. Not all household survival strategies are able to improvethe welfare of the household.
Keywords: bomb, coping, welfare, survival, consolidation, accumulation